To subtract \(4.66 \times 10^{-5} - 7.34 \times 10^{-7}\), we should first express both numbers with the same exponent.
Since \(4.66 \times 10^{-5}\) can be rewritten in terms of \(10^{-7}\):
\[ 4.66 \times 10^{-5} = 4.66 \times 10^{-5} \times \frac{100}{100} = 4.66 \times 10^{-5} \cdot 10^{2} = 466 \times 10^{-7} \]
Now, we can perform the subtraction:
\[ 466 \times 10^{-7} - 7.34 \times 10^{-7} = (466 - 7.34) \times 10^{-7} = 458.66 \times 10^{-7} \]
Now, we convert this back to the standard scientific notation:
\[ 458.66 \times 10^{-7} = 4.5866 \times 10^{-5} \]
So, the answer is:
\[ 4.5866 \times 10^{-5} \]
Thus, the correct response is:
4.5866×10^−5 (which is also expressed as "4.5866 times 10 superscript negative 5 baseline").